Categorical emotion recognition from voice improves during childhood and adolescence. Issue 1 (December 2018) - Grosbras, Marie-Hélène; Ross, Paddy; Belin, Pascal
Abstract Converging evidence demonstrates that emotion processing from facial expressions continues to improve throughout childhood and part of adolescence. Here we investigated whether this is also the case for emotions conveyed by non-linguistic vocal expressions, another key aspect of social interactions. We tested 225 children and adolescents (age 5–17) and 30 adults in a forced-choice labeling task using vocal bursts expressing four basic emotions (anger, fear, happiness and sadness). Mixed-model logistic regressions revealed a small but highly significant change with age, mainly driven by changes in the ability to identify anger and fear. Adult-level of performance was reached between 14 and 15 years of age. Also, across ages, female participants obtained better scores than male participants, with no significant interaction between age and sex effects. These results expand the findings showing that affective prosody understanding improves during childhood; they document, for the first time, continued improvement in vocal affect recognition from early childhood to mid- adolescence, a pivotal period for social maturation.